Percentage of Appearance of Physical Condition Applications for Badminton Athletes Aged 10-12 Years Old Based on Android Smartphone - Titis Pambudi; Setya Rahayu; Siti Baitul Mukarromah (Nicolaus Copernicus University in Toruń, 2022)
Badminton games can run well, mastery of techniques or basic game skills is needed. Badminton players must also have good physical abilities. There needs to be an application that supports the performance of the coach. The purpose of creating a product is to realize an attractive design for coaches, especially badminton. The purpose of this study was to determine the percentage of physical condition application displays for badminton athletes aged 10-12 years based on android smartphones. This study uses a survey-based quantitative descriptive method. The population of this study consisted of coaches at badminton clubs in Boyolali District. The sample in this study amounted to 15 coaches at the badminton club in Boyolali Regency were taken using a purposive sampling technique. Data collection techniques in this study used a questionnaire instrument with a Likert scale. Data analysis used SPSS version 25. The results showed that the percentage of physical condition application displays for badminton athletes aged 10-12 years based on Android smartphones in the very good category obtained a percentage of 93.33% with a total of 14 coaches and a good percentage of 6.67 % with a total of 1 coach. So it can be concluded that this application has a very good appearance in the view of the badminton coach.